2015
DOI: 10.1088/0952-4746/35/4/869
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the doses received by members of the public in Japan following the nuclear accident at Fukushima Daiichi nuclear power plant

Abstract: The earthquake and tsunami on 11 March 2011, centred off the east coast of Japan, caused considerable destruction and substantial loss of life along large swathes of the Japanese coastline. The tsunami damaged the Fukushima Daiichi nuclear power plant (NPP), resulting in prolonged releases of radioactive material into the environment. This paper assesses the doses received by members of the public in Japan. The assessment is based on an estimated source term and atmospheric dispersion modelling rather than mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Fujimura et al also reported that children between the ages of 0 and 15 years (n = 4,571) had a mean radiation dose of 1.5 mSv/year 6 months after the disaster, 1.5 mSv/year in 2012, 1.0 mSv/year in 2013, and 0.65 mSv/year in 2014, in Nihonmatsu City in Fukushima Prefecture 71) . Bedwell et al assessed the doses received by members of the public in Japan following the nuclear accident at the Fukushima Daiichi Nuclear Power Plant and demonstrated that across most of Japan the estimates of the dose were very low, and were estimated to be less than the annual average dose from natural background radiation in Japan 72) . Even in regions closest to the Fukushima Daiichi Nuclear Power Plant, the maximum lifetime effective dose is estimated to be well below the cumulative natural background dose over the same period 72) .…”
Section: ) By What Mechanism Could the Accident Increase The Incidenmentioning
confidence: 99%
See 2 more Smart Citations
“…Fujimura et al also reported that children between the ages of 0 and 15 years (n = 4,571) had a mean radiation dose of 1.5 mSv/year 6 months after the disaster, 1.5 mSv/year in 2012, 1.0 mSv/year in 2013, and 0.65 mSv/year in 2014, in Nihonmatsu City in Fukushima Prefecture 71) . Bedwell et al assessed the doses received by members of the public in Japan following the nuclear accident at the Fukushima Daiichi Nuclear Power Plant and demonstrated that across most of Japan the estimates of the dose were very low, and were estimated to be less than the annual average dose from natural background radiation in Japan 72) . Even in regions closest to the Fukushima Daiichi Nuclear Power Plant, the maximum lifetime effective dose is estimated to be well below the cumulative natural background dose over the same period 72) .…”
Section: ) By What Mechanism Could the Accident Increase The Incidenmentioning
confidence: 99%
“…Bedwell et al assessed the doses received by members of the public in Japan following the nuclear accident at the Fukushima Daiichi Nuclear Power Plant and demonstrated that across most of Japan the estimates of the dose were very low, and were estimated to be less than the annual average dose from natural background radiation in Japan 72) . Even in regions closest to the Fukushima Daiichi Nuclear Power Plant, the maximum lifetime effective dose is estimated to be well below the cumulative natural background dose over the same period 72) .…”
Section: ) By What Mechanism Could the Accident Increase The Incidenmentioning
confidence: 99%
See 1 more Smart Citation
“…While a lot work is published on the exposure of personnel working at nuclear power plants and the public around the facility, and the impact on the environment, in the event of a radiation accident [1][2][3], there is little published on acute radiation overexposure of the operators. Coeytaux et al compiled the reported radiation overexposure accidents worldwide in the period 1980-2013, from various sources in various fields including the nuclear industry [4].…”
Section: Introductionmentioning
confidence: 99%